2009
DOI: 10.1111/j.1349-7006.2009.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of docetaxel in patients with hepatic dysfunction treated in an oncology practice

Abstract: To investigate the relationship between the degree of liver dysfunction and the pharmacokinetics of docetaxel, a population pharmacokinetic model was developed in an oncology practice without excluding patients with moderate to severe liver dysfunction. Two hundred patients were treated with docetaxel as a single agent or in combination chemotherapy. The plasma concentration-time course data were analyzed using a three-compartment open model with zero-order administration and first-order elimination on the NON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 30 publications
3
33
0
Order By: Relevance
“…(4) In observational and retrospective studies, docetaxel clearance is reduced by 12-38% in patients with elevated plasma levels of TB and ⁄ or transaminases. (5,6) Bruno et al (7) showed that clearance was reduced by 27% in patients with ALT or AST >1.59 ULN and ALP >2.59 ULN. In a previous issue in this journal, Minami et al (6) recommended dose reduction by approximately 20% and 40% in patients with grade 2 and 3 elevations of transaminases and elevated ALP based on population PK modeling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(4) In observational and retrospective studies, docetaxel clearance is reduced by 12-38% in patients with elevated plasma levels of TB and ⁄ or transaminases. (5,6) Bruno et al (7) showed that clearance was reduced by 27% in patients with ALT or AST >1.59 ULN and ALP >2.59 ULN. In a previous issue in this journal, Minami et al (6) recommended dose reduction by approximately 20% and 40% in patients with grade 2 and 3 elevations of transaminases and elevated ALP based on population PK modeling.…”
mentioning
confidence: 99%
“…(5,6) Bruno et al (7) showed that clearance was reduced by 27% in patients with ALT or AST >1.59 ULN and ALP >2.59 ULN. In a previous issue in this journal, Minami et al (6) recommended dose reduction by approximately 20% and 40% in patients with grade 2 and 3 elevations of transaminases and elevated ALP based on population PK modeling. Importantly, as Minami and colleagues noted, this recommendation needs to be validated prospectively.…”
mentioning
confidence: 99%
“…Docetaxel clearance of each patient was obtained from the PPK study of docetaxel developed for Japanese cancer patients. 12) An LBR was performed by a generalized linear modeling method with the log link function and the error term which has a binomial distribution.…”
Section: Log-binominal Regression For Febrile Neutropenia Occurrencementioning
confidence: 99%
“…The PPK model of docetaxel developed for Japanese cancer patients is a 3-compartment model with aˆrst-order elimination. 12) The pharmacokinetic model was parameterized in terms of CL (clearance), the volume of distribution of the central compartment (V 1 ) as well as those of two peripheral compartments (V 2 and V 3 ) and intercompartment clearances (Q 2 and Q 3 ). A log-normal distribution was assumed for the inter-individual variabilities of CL, V 1 , V 3 and Q 3 .…”
Section: Settings Of Clinical Trial Simulation Platformmentioning
confidence: 99%
See 1 more Smart Citation